1996
DOI: 10.1203/00006450-199603000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intrauterine Pulmonary Hypertension Alters Endothelin Receptor Activity in the Ovine Fetal Lung

Abstract: Although endothelin (ET) contributes to the regulation of pulmonary vascular tone in the normal fetus, little is known about its role in pulmonary hypertension in the perinatal period. To examine the role of the ETB receptor in the normal ovine fetal lung, we studied the hemodynamic effects of ET-3 (a selective ETB receptor agonist) before and after RES-701 (a selective ETB receptor antagonist). RES-701 (10 mu g/min for 10 min) did not change basal pulmonary tone and blocked pulmonary vasodilation to ET-3 (500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
1
43
1
Order By: Relevance
“…Similar findings were reported in an ovine model of pulmonary hypertension (16) and in human neonates with pulmonary hypertension (14). This differs from our previous report (15), in which we did not find an increase in ET-1 circulating levels with hypoxia, although receptor studies suggested that ET-1 levels must be increased.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Similar findings were reported in an ovine model of pulmonary hypertension (16) and in human neonates with pulmonary hypertension (14). This differs from our previous report (15), in which we did not find an increase in ET-1 circulating levels with hypoxia, although receptor studies suggested that ET-1 levels must be increased.…”
contrasting
confidence: 57%
“…Supporting its role in the pathogenesis of PPHN, high circulating levels of ET-1 have been found in newborns with PPHN (14). Furthermore, it has been shown that pulmonary hypertension in neonatal animals is associated with a loss of ET B -mediated vasodilation, sustained ET Amediated vasoconstriction, and increased lung ET-1 content (15)(16)(17).…”
mentioning
confidence: 99%
“…Ductus arteriosus ligation causes progressive pulmonary hypertension as previously shown (13). Mean MPA pressure in the normal fetus at this gestational age is 43 Ϯ 4 mmHg (13).…”
Section: Resultsmentioning
confidence: 82%
“…In the normal fetal lung, ET-1 is present, and contributes to high PVR (9)(10)(11)(12). We have previously shown that chronic intrauterine pulmonary hypertension causes the loss of ET Bmediated vasodilation, progressive ET A -mediated vasoconstriction, and increased lung ET-1 content (13). Little is known, however, about the role of ET-1 and its receptors in chronic pulmonary hypertension in the perinatal period.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation